Total Physical Response - Sojuangon Rambe (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
Total Physical Response is a language teaching method emerged in 1970s, created by J.E. Asher. This method attempts to adapt the process of infants’ first language acquisition, into the teaching of second and foreign language. Asher claims that kids acquire their first language by listening to their parents commands, comprehending, executing, and then uttering the words. It implicates in the creation of language teaching material in form of lists of imperative sentences graded based on the grammatical complexity, which causes TPR seems to be a grammar based method. Attempts to imitate first language acquisition in second or foreign language classes practically requires the teacher to demonstrate at the same time as uttering commands to be acted by the student, in which the students are not required to repeat the words. It is considered as the reflection of what happens when children communicate with their parents. In spite of the deep first language acquisition adoption, J.E. Asher claims that TPR teaching practice is based on three principles which cover the relationship between physical and brain activity, involvement of left brain and right brain, and creation of free stress learning atmosphere.